2019
DOI: 10.1148/radiol.2018180910
|View full text |Cite
|
Sign up to set email alerts
|

Perinodular and Intranodular Radiomic Features on Lung CT Images Distinguish Adenocarcinomas from Granulomas

Abstract: Purpose: To evaluate ability of radiomic (computer-extracted imaging) features to distinguish non-small cell lung cancer adenocarcinomas from granulomas at noncontrast CT. Materials and Methods: For this retrospective study, screening or standard diagnostic noncontrast CT images were collected for 290 patients (mean age, 68 years; range, 18–92 years; 125 men [mean age, 67 years; range, 18–90 years] and 165 women [mean age, 68 years; range, 33–92 years]) from two institutions between 2007 and 2013. Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
222
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(235 citation statements)
references
References 36 publications
6
222
2
5
Order By: Relevance
“…The reported results indicated an accuracy of 86% in distinguishing lung cancer types, e.g., adenocarcinoma and squamous cell carcinoma [20]. Surprisingly, the reported results [21] in distinguishing non-small cell lung cancer adenocarcinomas from granulomas on non-contrast CT images showed that the developed CADx systems outperformed the radiologist readers. Joo et al [22] developed a CADx system using an ANN for breast nodule malignancy diagnosis in US images.…”
Section: Computer-aided Diagnosismentioning
confidence: 92%
See 3 more Smart Citations
“…The reported results indicated an accuracy of 86% in distinguishing lung cancer types, e.g., adenocarcinoma and squamous cell carcinoma [20]. Surprisingly, the reported results [21] in distinguishing non-small cell lung cancer adenocarcinomas from granulomas on non-contrast CT images showed that the developed CADx systems outperformed the radiologist readers. Joo et al [22] developed a CADx system using an ANN for breast nodule malignancy diagnosis in US images.…”
Section: Computer-aided Diagnosismentioning
confidence: 92%
“…Numerous studies [19][20][21][22] have demonstrated the application of CADx tools for diagnosing lung [19][20][21] and breast [19,22] lesions. Cheng et al [19] investigated the deep learning capability for the diagnosis of breast lesions in ultrasound (US) images and pulmonary nodules in CT scans.…”
Section: Computer-aided Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Two algorithms developed by Madabhushi's group analysed data from the CT scans of 290 people with one condition or the other. The first algorithm, which assessed the shape, texture and density of nodules and features around them, got it right 80% of the time 5 . The second, which analysed how twisted nearby blood vessels were (a marker of malignancy), scored 85% 6 .…”
Section: Anant Madabhushi Take a Riskmentioning
confidence: 99%